Unmanned aerial vehicles as an efficient platform to enable agriculture's digital future - Mwesigwa, Grace Elisha (Cranfield University, 2023)
The potential for Unmanned Aerial Vehicles to revolutionise agriculture, particularly small-scale farms, is enormous. Today, most agriculture UAVs are bulky, expensive, and primarily designed for heavy-lift applications, making them unaffordable for most small-scale farmers. Despite the availability of smaller UAVs, they were not designed for agricultural purposes, and have limited endurance. This project presents an innovative solution that involves integration of cylindrical Li-ion cells into the multirotor’s airframe structure, thereby cost- effectively enhancing endurance. Through the proposed engineering design approach, a prototype UAV is built and tested, demonstrating a significant endurance improvement over similarly sized vehicles powered by LiPo batteries. This design presents a budget friendly solution that could enable small-scale farmers to take advantage of affordable UAV technology.
Ignatyev, Dmitry I. - Associate Supervisor
Keywords: UAV; Endurance; Cylindrical Cell battery; Li-ion battery; 18650; Multirotor